Reanalysis of the cosmic dust L 2011 S2 and L 2009 I14 NASA samples - KAPIŠINSKÝ, Igor; IVAN, Juraj; IŽDINSKÝ, Karol; PÁNEK, Zdeněk; ZEMÁNKOVÁ, Milina (Contributions to Geophysics and Geodesy, 2021)
In this study the cosmic dust samples L 2011 S2 and L 2009 I14 have been reanalysed. Particles were obtained from the NASA Johnson Space Center(JSC) Cosmic Dust Collection. The reanalysis of the particle L 2009 I14 near the equilibrium state shows the 6.7 mass % of SiO2, and 60; 16.7; 5.4 and 11.2 mass % of pyroxene, cordierite pentlandite and iron silicide Fe2Si, respectively. In the case far from equilibrium state there can not be excluded a presence of other phases as bronzite or hypersthene or klinoferrosilite as well as troilite and pyrrhotite and sluggish crystallised pyroxene. For particle L 2011 S2 it was not possible to make any reliable qualitative conclusions due to problems mentioned in the paper.